1972
DOI: 10.1099/00221287-73-1-55
|View full text |Cite
|
Sign up to set email alerts
|

A Co-operative Numerical Analysis of Rapidly Growing Mycobacteria

Abstract: SUMMARYA co-operative numerical taxonomic analysis of rapidly growing mycobacteria of Runyon's group IV is reported. There was no limitation on the number, nature, or method of performance of the test characters contributed by each of the 12 participants. Initially 415 test characters were coded for analysis; deletion of irrelevant and repetitious data resulted in a final 195 characters used to generate the matching matrix. All nine major clusters defined in the study were of named species; however, three of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
2
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 23 publications
(17 reference statements)
2
84
2
1
Order By: Relevance
“…Eighty of the test cultures were assigned to the 'rhodochrous complex' (Table 2a,b,c below) and of the 20 marker strains 12 had been classified in the genus Mycobacterium; most of them were rapidly growing mycobacteria belonging to Runyon's group IV (Kubica et al 1972) and eight were in the genus Nocardia (Table I). Where possible the marker strains were type cultures.…”
mentioning
confidence: 99%
“…Eighty of the test cultures were assigned to the 'rhodochrous complex' (Table 2a,b,c below) and of the 20 marker strains 12 had been classified in the genus Mycobacterium; most of them were rapidly growing mycobacteria belonging to Runyon's group IV (Kubica et al 1972) and eight were in the genus Nocardia (Table I). Where possible the marker strains were type cultures.…”
mentioning
confidence: 99%
“…Two subspecies, cheLonae and abscessu.s. have been identified (11), although recent DNA studies suggest that they should be considered as distinct species (12) . M cheLonaewas first reported as a cause of human disease by Moore and Frerichs in 1953 (13).…”
Section: Discussionmentioning
confidence: 99%
“…In the former cooperative study, Kubica et al (5) suggested that strains containing representative cultures of both M . uaccae (2) and M .…”
Section: Discussionmentioning
confidence: 99%